Tourism in Malaysia: problems and prospects in context to socio-cultural and environmental surroundings of the country - Karim, A.H.M Zehadul; Md. Noon, Hazizan; Mohd Noor, Noor Azlan; Mohamad Diah, Nurazzura; Mustari, Sohela (Serials Publications, 2014)

(untitled)
Malaysia perhaps one of the most unique countries of the world, being strategically situated on the gate-way location of global routes with a wonderful eco-environmental setting. Being a pluralistic sosiety, Malaysia inherits its own traditional culture with harmonious integration of the diverse ethnic groups living in a very peaceful and politically stable situation. With the all its economic potentials, Malaysia has recently emerged as a newly-developed nation with a huge infrastructural growth in its industrial and manufacturing sectors. Due to these developments aand other eloquent features, people from abroad become largely attracted to this land and thus, they frequently arrive here as visitors and tourists. As recently as in the year 2005, it is reported that at least 16.7 million international tourists from outside visited Malaysia bringing about 30 billion ringgit in terms of foreign currency in this country. It brings civic pride and social prestige for Malaysia by making a kind of international linkages in global context. It takes Malaysian culture abroad and people from outside can get in touch of the unique Muslim heritage in modern Malaysia context. And thus it generates a discourse to conceptualize a rational framework for Malaysian tourism.